An X-ray spectroscopic search for dark matter and unidentified line signatures in the Perseus cluster with Hitomi. (27th March 2019) - Tamura, Takayuki; Fabian, Andrew C; Gandhi, Poshak; Gu, Liyi; Kamada, Ayuki; Kitayama, Tetsu; Loewenstein, Michael; Maeda, Yoshitomo; Matsushita, Kyoko; McCammon, Dan; Mitsuda, Kazuhisa; Nakashima, Shinya; et al.
Abstract: The reported detection of a 3.5 keV emission signal in the Perseus cluster core by Bulbul et al. (2014, ApJ, 789, 13) was ruled out at high confidence in analysis conducted by Aharonian et al. (2017, ApJ, 837, L15) of X-ray spectra at 5 eV energy resolution obtained with the Hitomi observatory Soft X-ray Spectrometer (SXS). Using the same data, we search the full 2–12 keV SXS energy band for previously unidentified emission and absorption features. No significant unidentified line emission or absorption is found. Line flux upper limits (1σ per resolution element) vary with photon energy and assumed intrinsic width, decreasing from ∼100 at 2 keV to <10 photons cm −2  s −1  sr −1 over most of the 5–10 keV energy range for a Gaussian line with Doppler broadening of 640 km s −1 . Limits for narrower and broader lines have a similar energy dependence and are systematically smaller and larger, respectively. These line flux limits are used to constrain the decay rate of hypothetical dark matter candidates. For the sterile neutrino decay rate, we place new constraints over the mass range of 4–24 keV with mass resolution better than any previous X-ray analysis. Additionally, the accuracy of relevant thermal spectral models and atomic data are evaluated. The Perseus cluster spectra may be described by a composite of multi-temperature thermal and active galactic nuclei (AGN) power-law continua. Superposed on these, a few line emission signals possibly originating from unmodeled atomic processes (including Si xiv and Fe xxv ) are marginally detected and tabulated. Comparisons with previous X-ray upper limits and future prospects for dark matter searches using high-energy resolution spectroscopy are discussed.